Stephan Balkenhol CAC Málaga Centro de Arte Contemporáneo de Málaga 19 enero-22 abril 2018 = 19 January-22 April 2018 - Balkenhol, Stephan 1957- (cacmálaga, 2017)
The exhibition features more than thirty sculptures selected from the most significant works the German artist has produced in recent years. Balkenhol, who has not shown his work in Spain for more than ten years, mainly uses wood to create his everyday figures and his sculptures bear visible traces of the carving process. The coarseness of the planed areas contrasts with the smoothness of the polished ones, generating a remarkable interplay of textures in his work. An eerie silence accompanies Balkenhol’s trademark and seemingly common figures. The artist invites viewers to try and discover the unique reality he creates
Keywords: Balkenhol, Stephan -- 1957-; Geschichte 2003-2017; Holzplastik; Balkenhol, Stephan 1957- / Exhibitions; Wood sculpture / Exhibitions / 21st century; Wood sculpture, German / Exhibitions / 21st century; Wood-carved figurines / Exhibitions; Human beings in art / Exhibitions; Ausstellungskatalog -- CAC Málaga, Centro de Arte Contemporáneo de Málaga -- 19.01.2018-22.05.2018 -- Malaga; Bildband